2022
DOI: 10.1609/icwsm.v16i1.19307
|View full text |Cite
|
Sign up to set email alerts
|

Closing Pandora’s Box on Naver: Toward Ending Cyber Harassment

Abstract: In reaction to the high-profile celebrity suicides of Sulli and Goo Hara in 2019, attributed to cyberbullying, Korea's most popular internet platform Naver introduced a range of self-regulatory measures to curtail targeted hate comments online in 2020. These regulations include removing the entertainment comment section and pseudonymizing users by revealing comment history but maintaining user anonymity. To take a closer look at celebrity cyberbullying and analyze the effects of Naver's novel self-regulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As a supplemental approach, online legal consultation, i.e., support from specialists, can be helpful. Displaying attitudes adopted by platforms to reject online harassment also inhibits toxic posts (Kang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a supplemental approach, online legal consultation, i.e., support from specialists, can be helpful. Displaying attitudes adopted by platforms to reject online harassment also inhibits toxic posts (Kang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could mitigate the stigma of online harassment (Mesch and Talmud, 2006;Andalibi et al, 2016;Foster and Fullagar, 2018), victimblaming (Scott et al, 2019;Hand, 2021), and propagating offensive behavior (Bliuc et al, 2018;Yokotani and Takano, 2021). Educating people accordingly can ameliorate the adverse effects of sensational coverage (Kang et al, 2022).…”
Section: Approaches Against Six Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable problems include cyber harassment and hate speech against minorities in comments sections along with news articles of questionable quality aiming to take advantage of algorithms. For instance, in March 2020, Naver removed sections where users could comment on its entertainment news stories, following criticisms against serious cyber harassment toward celebrities (Kang et al, 2022). Hate speech against minority groups in comment sections is also increasingly widespread; exposure to hate speech can bring about harmful effects, ranging from going along with the stereotypes to avoiding news stories of and comments on a given issue (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on design features that explicitly structure discussions, Rho et al [99] showed that the design input of political hashtags on social media influenced the deliberative quality of online discussions causing an increase in emotional and more black-and-white rhetoric. Kang et al discuss various policy changes on the South Korean platform Naver including the removal of negative emoticons that aimed to reduce the amount of abusive and offensive comments [70]. Kriplean et al [74] built a platform called ConsiderIt that helped users understand previous user posts.…”
Section: Reaction Mechanisms Digital Environments and Political Disco...mentioning
confidence: 99%